2022
DOI: 10.3389/fonc.2022.849004
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Novel Pathomechanism in PEComa by the Loss of Heterozygosity of TP53

Abstract: Since the introduction of next-generation sequencing, the frequency of germline pathogenic TP53 variants and the number of cases with unusual clinical presentations have been increasing. This has led to the expansion of the classical Li–Fraumeni syndrome concept to a wider cancer predisposition syndrome designated as the Li–Fraumeni spectrum. Here, we present a case with a malignant, metastatic perivascular epithelioid cell tumor (PEComa) of the thigh muscle and a sinonasal carcinoma harboring a novel TP53 ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Galera López et al reported a simultaneous diagnosis of PEComa of the liver in two siblings with an LFS ( 23 ). Butz et al reported a malignant, metastatic PEComa of the thigh muscle harboring a novel TP53 germline splice mutation in an attenuated LFS patient ( 24 ). Our case is the first uterine PEComa with related LFS.…”
Section: Discussionmentioning
confidence: 99%
“…Galera López et al reported a simultaneous diagnosis of PEComa of the liver in two siblings with an LFS ( 23 ). Butz et al reported a malignant, metastatic PEComa of the thigh muscle harboring a novel TP53 germline splice mutation in an attenuated LFS patient ( 24 ). Our case is the first uterine PEComa with related LFS.…”
Section: Discussionmentioning
confidence: 99%
“…Bidirectional Sanger sequencing of the coding exons and exon-intron boundaries of the APC gene and multiplex ligation-dependent probe amplification (MLPA) testing for copy number variants by P043-E1 kit (MRC-Holland, The Netherlands) were performed. Whole exome sequencing was done as previously described [6,7] (see Supplementary Methods). Whole genome sequencing (WGS) was designed as a duo of the disease-affected proband and his nonaffected brother (details in Supplementary Methods).…”
Section: Methods Family Selection and Germline Genetic Screeningmentioning
confidence: 99%
“…Research into most PEComas instances has revealed that mutations in TP53 often occur alongside alterations in TSC1/TSC2, TFE3, and other genes involved in PEComa development, with these gene mutations not being the sole cause of PEComas [24][25][26]. Recent research has pinpointed PEComas with TP53 mutations, absent of simultaneous TSC mutations or TFE3 rearrangements [27], indicating TP53's possible role as a key influencer in PEComa's emergence. Nonetheless, additional studies are required to de-termine if mutations in TP53 solely serve as the fundamental cause of PEComas without TSC mutations or TFE3 rearrangements [28,29].…”
Section: Tp53 Mutationmentioning
confidence: 99%